Examining derivatives of quinacridone, diketopyrrolopyrrole and indigo as the visible-light organic photocatalysts for metal-free atom transfer radical polymerization - Jia, Tao (2021)
Conventional atom transfer radical polymerization (ATRP) involving metal/ligand complexes as the catalysts has been widely used for synthesis of myriads of polymers with controllable molecular weights, monomer sequences and chain end groups, but suffers from the metal-contamination in the final polymer products. This issue has been recently mediated to some extent by using organic photocatalysts, which not only enable controllable polymerization upon light irradiation, but also offers spatiotemporal control of the polymerizations. To date the majority of reported organic photocatalysts for ATRP mainly absorb light in the UV region. Here we examined three organic chromophores, quinacridone, diketopyrrolopyrrole and indigo, as visible-light-absorbing organic photocatalysts for controllable polymerization of a series of methacrylates monomers via a scheme of light-mediated ATRP. Among the three types of organic chromophores, N,N-bis(tert-butyloxycarbonyl) quinacridone shows the highest fluorescence quantum yield and the best electrochemical and optical stability, all of which contribute to its outstanding performance in controllable polymerization of methacrylates under visible LED light irradiation.